2018
DOI: 10.1074/jbc.ra118.002853
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8 N termini influence pore properties and gating of volume-regulated anion channels (VRACs)

Abstract: Volume-regulated anion channels (VRACs) are crucial for cell volume regulation and have various roles in physiology and pathology. VRACs were recently discovered to be formed by heteromers of leucine-rich repeat–containing 8 (LRRC8) proteins. However, the structural determinants of VRAC permeation and gating remain largely unknown. We show here that the short stretch preceding the first LRRC8 transmembrane domain determines VRAC conductance, ion permeability, and inactivation gating. Substituted-cysteine acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 58 publications
7
54
0
Order By: Relevance
“…Most subunit composition-specific properties relate to pore-intrinsic features of channels such as voltage-dependent inactivation kinetics, single-channel conductance, and substrate selectivity. Together with point mutations altering ion selectivity ( 3 , 24 , 25 , 26 ) and the successful reconstitution of VRAC currents by purified LRRC8 complexes in lipid bilayers ( 24 ), this demonstrates that LRRC8 complexes are indeed the pore-forming unit of VRACs.…”
Section: Main Textmentioning
confidence: 92%
See 1 more Smart Citation
“…Most subunit composition-specific properties relate to pore-intrinsic features of channels such as voltage-dependent inactivation kinetics, single-channel conductance, and substrate selectivity. Together with point mutations altering ion selectivity ( 3 , 24 , 25 , 26 ) and the successful reconstitution of VRAC currents by purified LRRC8 complexes in lipid bilayers ( 24 ), this demonstrates that LRRC8 complexes are indeed the pore-forming unit of VRACs.…”
Section: Main Textmentioning
confidence: 92%
“…In the few years after their molecular identification ( 3 , 4 ), tremendous insight into the biophysics of VRACs was obtained using molecular biological tools in mammalian cells and Xenopus oocytes ( 24 , 25 , 26 , 27 , 28 , 29 ). VRACs were reconstituted from purified LRRC8 complexes in droplet lipid bilayers ( 24 ), and the structures of LRRC8 complexes have recently been resolved ( 30 , 31 , 32 , 33 ).…”
Section: Main Textmentioning
confidence: 99%
“…To note, this article was submitted after the publication of several articles that show the hexameric structure of LRRC8A, mainly using cryo-electron microscopy (Deneka et al, 2018;Kasuya et al, 2018;Kefauver et al, 2018), and suggest an involvement of LRRC8 in the VSOR pore using LRRC8 2/2 HEK293 cells (Deneka et al, 2018) and HCT116 cells (Yamada and Strange, 2018;Zhou et al, 2018). Deneka et al (2018) showed that the hexameric structure, which incorporates a pore-like, vase-shaped conformation, can be formed by purified recombinant LRRC8A alone or together with LRRC8C.…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 99%
“…Yamada and Strange (2018) showed that a 25-aminoacid sequence unique to the intracellular loop of LRRC8A plays a role in VSOR pore structure and function. On the other hand, Zhou et al (2018) demonstrated that the N termini of the LRRC8A/8C heteromer participate in forming the cytosolic portion of the VSOR pore. However, changes in the anion selectivity sequence and the anion/cation permeability ratio were not observed in these studies and are to be examined in future studies.…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 99%
“…Might these differences be related to gating conformational changes? Gating in LRRC8 and related connexin and innexin channels is thought to involve the N-terminus prior to the beginning of TM1 (Kefauver et al, 2018a;Oshima, 2014;Zhou et al, 2018), whereas sensing of internal ionic strength is thought to occur in the cytoplasmic LRRs or connection between linker helices 2 and 3 (Syeda et al, 2016). Notably, the conformational changes we observe between constricted and expanded states couple these presumed sensing and gating elements.…”
Section: Dcpib Inhibits Lrrc8a Through a Cork-in-bottle Mechanismmentioning
confidence: 80%